(untitled) (International relations and international law Journal, 2024)
This research paper examines the role of the China-Pakistan Economic Corridor (CPEC) in reshaping Pakistan’s economic landscape. It aims to shed light on arising insights within the rivalries dilemmas amidst global powers, particularly those countering China’s Belt and Road Initiative (BRI) through diplomatic strategies. As CPEC is an element of the BRI, the study is vital in understanding the ongoing race for influence and power. The China-Pakistan Economic Corridor (CPEC) highlights the economic cooperation between China and Pakistan, performing as a beacon of regional mapping and economic dynamics as the largest and most comprehensive bilateral initiative. The findings of this study would spark a fresh discourse on Pakistan’s economic legacy, contributing significantly to the narrative within South Asia. However, the research would employ a descriptive method of inquiry, collecting secondary data from manifold reputable journals. The research would be beneficial in exploring alternative facets of Pak-China relations and addressing additional regional challenges. Yet, it benefits in pinpointing novel avenues for scholars, experts, and policy-making institutions. Ultimately, the findings are crucial in highlighting issues concerning peace, cordiality, and cohesion within the region. Moreover, the research outcomes would further unlock opportunities for future investigations. Key words: Economics Landscape, Role of CPEC, Pakistan, China